2001
DOI: 10.1034/j.1600-0404.2001.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of discharge to home during the first year after right hemisphere stroke

Abstract: Hemiparesis, unawareness of illness and presence of a relative at home were the best predictors of the time from right hemisphere stroke to discharge to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 27 publications
1
57
4
2
Order By: Relevance
“…Denes et al 8 and Pinedo Otaola and De La Villa 14 showed that A does not affect functional recovery after stroke. Jehkonen et al 6 found that neither A for hemiparesis nor A for neglect are important predictors connected with the return to home after right hemisphere stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Denes et al 8 and Pinedo Otaola and De La Villa 14 showed that A does not affect functional recovery after stroke. Jehkonen et al 6 found that neither A for hemiparesis nor A for neglect are important predictors connected with the return to home after right hemisphere stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies by Pedersen et al, 5 Jehkonen et al, 6 and Maeshima et al, 7 the assessment of N and A was done during the first days after stroke. This allowed the inclusion in the study of patients with possible neuropsychological deficits, which were not defined yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This deficit has been reported to occur in approximately 38% of individuals with RHD admitted to a rehabilitation unit . Individuals who are not aware of their deficits or have poor insight into potential consequences of their deficits are not as likely to actively participate in therapy and often have poorer outcomes (Hartman-Maeir, Soroker, Oman, & Katz, 2003;Jehkonen et al, 2001;Noe, Ferri, Caballero, Villodre, Sanchez, & Chirivella, 2005). Cherney (2006) describes a framework for clinical decision making for clients with anosognosia that involves consideration of medical factors, client preferences, issues of quality of life, and other external/contextual factors.…”
Section: Treatment Selection Based On Deficits Not Etiologymentioning
confidence: 99%
“…Preservation of language function is considered one of the primary reasons for a higher percentage of right alicted people returning to work; however, this cohort of patients are usually the one who most frequently develop social shortcomings in contrast to the left-sided stroke patients [50]. Further studies with exclusion of hemineglect patients may help to exemplify the diference in the disabilities between left and right hemisphere stroke patients [51].…”
Section: Right Versus Left Hemisphere Strokementioning
confidence: 99%